M.F.K. Fisher, Julia Child, and Alice Waters : celebrating the pleasures of the table - Reardon, Joan, 1930- (Harmony Books, 1994)
M. F. K. Fisher, Julia Child, and Alice Waters celebrates the accomplishments and friendships of three women who changed the way Americans think about food and cooking, dining and pleasure. In a series of three overlapping biographical portraits, Reardon reveals the private lives behind their public personas. Tracing major developments in their careers and quoting extensively from letters they exchanged, she recounts the times and places at which their lives intersected and shares testimonies of the friendship and respect that grew among them.